The Influence of Social Cohesion and Attitudes on Community Preparedness in the Face of A Tsunami Disaster - Johan Budhiana; Fera Melinda; Maria Yulianti; Rosliana Dewi; Iwan Permana (Indonesian Journal of Global Health Research, 2025)
Indonesia is a country located at the confluence of the world's three tectonic plates, making a number of areas directly adjacent to the zone highly vulnerable to earthquake and tsunami disasters. Preparedness is a series of activities carried out to anticipate disasters. There are several factors that influence community preparedness, namely social cohesion and attitude. Objective: The purpose of this study was to determine the effect of social cohesion and attitudes on community preparedness for tsunami disasters. Methods: Type of correlational research with a cross sectional approach. The population was all people in Kedusunan Sawah Garung, Loji Village, Simpenan Subdistrict with a sample of 300, using proportional random sampling technique. Data collection techniques using questionnaires. Data analysis using simple linear regression and multiple linear regression. Results: The results showed that there was an influence of social cohesion (p=0.000) and attitude (p=0.000) on community preparedness. There is a simultaneous influence of social cohesion (p=0.000) and attitude (p=0.002) on community preparedness. Conclusion: social cohesion and attitudes towards community preparedness. It is expected that Loji Village and BPBD Sukabumi Regency can improve community preparedness through activities such as training, seminars, workshops related to natural disasters, especially tsunami disasters.